The mortality from tuberculosis in Saorstat Eireann: a statistical study - Geary, R. C. (Statistical and Social Inquiry Society of Ireland, 1930)
There were 3,774 deaths from tuberculosis in Saorstat Eireann in 1929, or 128 per 100,000 of the estimated population. For the fourth year in succession declines have been recorded. The rate in 1929 was 6.6% less than the rate in 1928, and 53.7% less than in 1904, which was the highest recorded in recent years in the present area of Saorstat Eireann. Deaths from tuberculosis were 8.8% of all deaths in 1929. Between the ages of 15 and 45 deaths from tuberculosis were no less than 42.8% of all deaths in 1928.
Read before the Society on Thursday, 19th June, 1930
Keywords: Tuberculosis; Mortality rates; 314.15